MODERN MUSLIMAH IN MEDIA: A STUDY OF RECEPTION ANALYSIS IN “SALIHA” PROGRAM ON NET TV - Eka Perwitasari Fauzi; Feni Fasta; Robert Jeyakumar Nathan; So Won Jeong (ASPIRATION Journal, 2020)
Indonesia, as a country with the largest Muslim population in the world, holds a significant market share of the Islamic industry, especially for Muslim women. This study discusses how media constructs meaning for modern Muslim women's identity, in "Saliha" a program aired on Indonesia national television, NET TV. This qualitative research is conducted based on social construction of reality theory and using Stuart Hall's reception analysis method. The data was obtained via in-depth interviews and Focus Group Discussion. Findings indicate shifting views of Muslim women portrayed in television; these findings add to the continuous mediatization of modern Muslims, especially women. Thus, the existence of Muslim women continued to negotiate and be redefined through images, narratives, and knowledge constructed in media for market consumption.